Thrombus Aspiration during ST-Segment Elevation Myocardial Infarction - Fröbert, Ole; Lagerqvist, Bo; Olivecrona, Göran K; Omerovic, Elmir; Gudnason, Thorarinn; Maeng, Michael; Aasa, Mikael; Angerås, Oskar; Calais, Fredrik; Danielewicz, Mikael; Erlinge, David; Hellsten, Lars; et al. (The New England journal of medicine, 2013)
The infrastructure of an established PCI registry was used to conduct a randomized trial comparing manual thrombus aspiration before PCI with PCI alone in patients with STEMI. There was no significant difference between the two groups in mortality at 30 days. One of the most important therapeutic challenges in the management of ST-segment elevation myocardial infarction (STEMI) is the establishment of normal coronary blood flow after percutaneous coronary intervention (PCI). Reduced flow is closely associated with reperfusion injury, 1 which can lead to arrhythmias, contractile dysfunction, microvascular impairment, and irreversible myocardial damage. 2 Reduced myocardial perfusion is also associated with heart failure and death. 3 , 4 Coronary-artery thrombus aspiration, a simple, rapidly performed, and relatively inexpensive adjunct to PCI, may improve blood flow and resolution of ST-segment elevation, 5 – 9 although this is not a universal finding. 10 – 12 Previous studies of thrombus aspiration have not . . .